Three temporalities inside the Phenomenology of Spirit (2007)
Following Hegel's own formulations about the diverse "histories" of the Fenomenology (history of "formation of consciousness", "real history" of spirit, "history of the world" and "concipient history"), three temporary structures of the work are studied: a) the temporality of natural consciousness, b) the temporality of the "system of configurations of consciousness" and c) the "external" temporality of the spirit. The positions of Peter Rohs and Edgardo Albizu are taken into account critically.